Negative chronotropic response to adenosine receptor stimulation in rat right atria after run training - Priviero, F.; De Nucci, G.; Antunes, E.; Zanesco, A. (Blackwell Publishing Asia, 2004)
The aim of the present study was to evaluate the potency and maximal responses (E-max) to the adenosine receptor agonists N-6-cyclopentyladenosine (CPA), N-ethylcarboxamidoadenosine (NECA) and N-6-(3-iodobenzyl)-5'-N-methylcarbaxamidoadenosine (IB-MECA) in right atria from trained rats. We also investigated the interaction between the training bradycardia and the sensitivity of the chronotropic response mediated by adenosine receptor stimulation.2. Animals were submitted to run training for 60 min, 5 days a week, over a period of 8 weeks. Mean blood pressure and heart rate were measured in conscious animals. Right atria were isolated and concentration-response curves to CPA, NECA and IB-MECA were obtained.3. A reduction in heart rate was found in trained rats, indicating that the training programme was successful in inducing physical conditioning. The three adenosine receptor agonists induced a concentration-dependent negative chronotropic response. The rank order of potency and E-max for the three adenosine receptor agonists was CPA>NECA>IB-MECA.4. Dynamic exercise for 8 weeks did not alter the E a, for CPA, NECA and IB-MECA. Similarly, the potencies of CPA and NECA were not affected by run training, whereas the potency of IB-MECA was reduced (6.10+/-0.09 vs 5.66+/-0.10 for sedentary and trained groups, respectively).5. In conclusion, run training for 8 weeks induced a desensitization of the chronotropic response to IB-MECA without changing the potency of CPA and NECA. These findings exclude the participation of adenosine receptors in the training bradycardia.
Keywords: adenosine agonist; dynamic exercise; heart rate; potency